Od nastoletniego macierzyństwa do życia w dorosłości w wypowiedziach kobiety z niepełnosprawnością intelektualną - Mach, Aleksandra (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
Maternity in the case of women with intellectual disabilities is exposed to many factors hindering its implementation. Research on this occurrence shows that one of the main reasons for that is insufficient or inept support for this group of women in different areas, such as educational, financial, informative, emotional. Teenage mothers with disabilities are in a particularly difficult situation. The article presents the analysis of statements of an adult woman with mild intellectual disability on her experience of teenage pregnancy as well as maternity as an adult woman. The humanistic attitude of giving the floor to the respondent allowed to determine other meaningful matters in the woman’s life (among others: relationships with life partners, relationship with the mother, vision of the future, financial situation) The methodology of research used was qualitative research. Two open interviews took place 8 months apart. The interviews were recorded to an electronic device. The material obtained was later transcribed. Triangulation of the sources was included (two family assistants were interviewed).